The Impact of Agriculture Credit on Growth in Pakistan - Akmal , Nadeem; Rehman , Bushra; Ali , Akhtar; Shah , Hassnain (Asian Journal of Agriculture and Rural Development, 2012)
Agriculture took place on land, where crops, rising and rearing animals for the production of food for man and industries. But to run all the activities credit is the main stream. In most of the developing countries credit played a very important role in economic growth. This study is designed to analyze the impact of agriculture credit on growth. This type of work was done in 2003 by Iqbal et al. and the same methodology is followed in this paper. Secondary data was taken from 1970-2010.Water availability; labour availability and crop intensity are the important determinants of agriculture GDP.